PENGARUH LIKUIDITAS, LEVERAGE, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PROFITABILITAS (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019) - Mulia Rahmah, S. Kom., M.Si.; Aryo Bagaskoro (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The research to test empirically the effect of Liquidity, Leverage, and Company’s Growth on Profitability of Manufacturing Companies in the Food and Beverages Sector Listed on the Indonesia Stock Exchange on 2015-2019. The research was conducted in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the 2015-2019 period. The sampling method used was purposive sampling method, the sample used was 17 companies. The data analysis technique used is descriptive statistics, classic assumption test, normally test, multicolonierity test, autocorrelation test, heteroscedasticity test, multiple liner regression model and hypothesis testing using SPSS 24 for windows. The result showed that Liquidity, Leverage, and Company’s Growth has simultaneously affect Profitability. In Parsial, Liquidity has a positive and significant effect on Profitability. Meanwhile, Leverage has a negative but insignificant effect on Profitability. And Company’s Growth has a positive and significant effect on Profitability